No causal genetic relationships between atrial fibrillation and vascular dementia: A bidirectional Mendelian randomization study - Gao, Ya-fang; Jin, Tian-yu; Chen, Yan; Ding, Ya-hui (Frontiers in Cardiovascular Medicine, 2023)
Background Numerous observational studies have suggested that atrial fibrillation (AF) was associated with an increased risk of vascular dementia (VaD). However, the causal genetic relationships between AF and VaD remains unclear. To evaluate the effect of AF on VaD, we performed the Mendelian randomization (MR) analysis to investigate the causal genetic relationships between AF and VaD. Methods The bidirectional MR analysis was conducted to explore the causal relationships between exposure and disease. We applied a series of quality assessments to select significantly and independently single nucleotide polymorphisms (SNPs) from publicly available large-scale genome-wide association studies (GWAS) databases. Three methods [Inverse variance weighted method (IVW), MR-Egger method, and weighted median (WM)method] were used to derive MR estimates. In order to ensure reliable MR results, sensitivity analyses were performed to evaluate the horizontal pleiotropy and heterogeneity. Results Our MR analyses revealed no significant genetic relationships between AF and the risk of VaD (IVW: OR = 1.10, 95%CI = 0.95–1.28, P = 0.20). In the reverse direction analysis, there was no evidence to support a significant genetic relationship of VaD with AF risk (IVW: OR = 1.00, 95% CI = 0.99–1.01, P = 0.52). Consistent results were obtained using different MR methods. Sensitivity analyses suggested no significant horizontal pleiotropy and heterogeneity in the study. Conclusion This MR analysis did not provide evidence to support the causal genetic relationships between AF on VaD risk and the causal effect of VaD on AF risk.